Threshold voltage of Ge channel MOSFETs with high-k gate insulator - Chun-Hsing Shih (Sweden, 2024)
As the MOSFET devices scale into nanoscale regime, it is increasingly difficult to enhance the performance of silicon CMOS devices through traditional scaling approaches. Ge channel MOSFETs with high -k gate insulator become one of most attracting candidates for the use in future CMOS technologies because of the high driving current enhancement [1,2]. However, the physical modeling of Ge channel MOSFETs suffers from severe challenges never seen before. Determining the physical threshold voltage remains problematic due to the use of Ge channel and high-k gate dielectrics. This work elucidates the difficulties in applying the conventional 2Psi threshold voltage model to high-k Ge-channel MOSFETs, and presents a physical drift-current threshold voltage model for the future applications of Ge MOSFETs.